From brain to worksite: the role of fNIRS in cognitive studies and worker safety - Han, Yang; Huang, Jianling; Yin, Yang; Chen, Huihua (Frontiers in Public Health, 2023)
Effective hazard recognition and decision-making are crucial factors in ensuring workplace safety in the construction industry. Workers’ cognition closely relates to that hazard-handling behavior. Functional near-infrared spectroscopy (fNIRS) is a neurotechique tool that can evaluate the concentration vibration of oxygenated hemoglobin [HbO2] and deoxygenated hemoglobin [HbR] to reflect the cognition process. It is essential to monitor workers’ brain activity by fNIRS to analyze their cognitive status and reveal the mechanism in hazard recognition and decision-making process, providing guidance for capability evaluation and management enhancement. This review offers a systematic assessment of fNIRS, encompassing the basic theory, experiment analysis, data analysis, and discussion. A literature search and content analysis are conducted to identify the application of fNIRS in construction safety research, the limitations of selected studies, and the prospects of fNIRS in future research. This article serves as a guide for researchers keen on harnessing fNIRS to bolster construction safety standards and forwards insightful recommendations for subsequent studies.